Effect of Visible‐Light Exposure and Electrolyte Oxygen Content on the Capacitance of Sulfur‐Doped Carbon. Issue 3 (13th August 2013) - Singh, Kavindra; Seredych, Mykola; Rodriguez Castellon, Enrique; Bandosz, Teresa J.
Abstract A high‐density and low‐surface‐area sulfur‐doped carbon material is tested as a supercapacitor in acidic and neutral media. The electrolytes that are used are either oxygenated or are exposed to atmospheric oxygen. The electrochemical capacitance is measured both in dark conditions and under simulated solar irradiation. The capacitance values are calculated after the first and the 20th cycles. After cycling, a significant increase in the capacitance is observed in both electrolytes, which is accompanied by clear oxidation of the carbon surface. Oxygen in the system and visible‐light irradiation considerably increases the performance. The enhancement in the capacitance is linked to the carbon texture and chemistry. Reduced sulfur that is incorporated into the carbon matrix promotes photogeneration of electrons and holes, and the latter have a positive effect on oxygen reduction reactions as the holes contribute to the oxidation of water and the formation of radicals. These processes lead to the oxidation of the carbon surface and the formation of pores in which charge can be stored. Changes in the chemistry of sulfur lead to a clear pseudocapacitive contribution, increasing the capacitance in the acidic medium.